2006
DOI: 10.1111/j.2042-3306.2006.tb05558.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a pre‐moistened multilayered breathable fabric in promoting heat loss during recovery after exercise under hot conditions

Abstract: A specially-designed, pre-moistened multilayered breathable fabric failed to promote evaporative cooling compared to negative control. Cold water baths may need to be repeated throughout recovery to optimise their effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…At a HR of 60 bpm point in time, the mean T c was still 38.7 ± 0.5°C (range 38.0–39.3°C) while 8/12 trotters still measured a T c higher than 38.5°C. A post-exercise peak T re was earlier reported in a few other studies ( Hodgson et al, 1993 ; Kohn and Hinchcliff, 1995 ; Marlin et al, 1996 , 1998 ; Kohn et al, 1999 ; Foreman et al, 2006 ; Verdegaal et al, 2017 ) and supports the conclusion that it is necessary to continue monitoring racehorses during recovery. Based on our findings and coupled with those reported by previous studies, continuous monitoring of racehorses and sport horses for hyperthermia using the GI pill or T re during a period of rest for at least 60 min post-exercise is highly recommended.…”
Section: Discussionsupporting
confidence: 85%
“…At a HR of 60 bpm point in time, the mean T c was still 38.7 ± 0.5°C (range 38.0–39.3°C) while 8/12 trotters still measured a T c higher than 38.5°C. A post-exercise peak T re was earlier reported in a few other studies ( Hodgson et al, 1993 ; Kohn and Hinchcliff, 1995 ; Marlin et al, 1996 , 1998 ; Kohn et al, 1999 ; Foreman et al, 2006 ; Verdegaal et al, 2017 ) and supports the conclusion that it is necessary to continue monitoring racehorses during recovery. Based on our findings and coupled with those reported by previous studies, continuous monitoring of racehorses and sport horses for hyperthermia using the GI pill or T re during a period of rest for at least 60 min post-exercise is highly recommended.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast to the human and equine literature, the application of water-soaked towels as a cooling technique appears frequently in online first aid recommendations for cooling dogs with HRI [ 23 , 24 , 37 ]. However, the cooling effects from application of water-soaked towels have been shown to be less rapid than cold-water immersion in humans [ 9 ], and ineffective in horses [ 38 ]. Empirical research evaluating the effectiveness of wet towels for cooling dogs is lacking, but clinical review articles have suggested that wet towels should be applied only to less-haired regions, such as the abdomen or inner thigh, because covering the entire dog in a towel (even if wet) could restrict air movement around the dog and reduce the potential for additional heat loss via evaporation and convection [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only are owners of brachycephalic dogs more likely to recognize thermoregulation problems (brachycephalic dogs were also considered to have higher summer CAS), they also appear to be more likely to utilize cooling aids such as cooling coats to facilitate activity in summer. This is concerning, as there is a paucity of peer-reviewed evidence relating to the effectiveness of canine cooling coats, and similar cooling aids (moistened multilayer breathable fabric coats) have been found to be ineffective when used on exercising horses [ 49 ]. Continued use of ineffective cooling aids could inadvertently put more dogs at risk of HRI, if owners believe the use of such devices could mitigate hot weather that would otherwise prevent them from exercising their dog.…”
Section: Discussionmentioning
confidence: 99%